2011
DOI: 10.1074/jbc.c111.257899
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Human ISG15 Protein in Complex with Influenza B Virus NS1B

Abstract: ISG15 (interferon-stimulated gene 15), the first ubiquitin-like protein (UBL) identified, has emerged as an important cellular antiviral factor. It consists of two UBL domains with a short linker between them. The covalent attachment of ISG15 to host and viral proteins to modify their functions, similar to ubiquitylation, is named ISGylation. Influenza B virus NS1B protein antagonizes human but not mouse ISGylation because NS1B exhibits species specificity; it only binds human and non-human primate ISG15. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…The K d was determined to be 656 nM +/− 242 nM (Supplemental Figure S3B); this is similar to the K d for the ICAM1-CD11a interaction (200–500 nM) (Shimaoka et al, 2001; Tominaga et al, 1998) and within the range for that reported for the ISG15-Influenza virus NS1B interaction (180 nM-1.9 μM) (Guan et al, 2011; Li et al, 2011). The binding of ICAM1 to the αI domain is dependent on the Metal Ion Dependent Adhesion Site (MIDAS), a group of residues that coordinate a magnesium ion at the ICAM1-αI interface (Shimaoka et al, 2003).…”
Section: Resultssupporting
confidence: 78%
“…The K d was determined to be 656 nM +/− 242 nM (Supplemental Figure S3B); this is similar to the K d for the ICAM1-CD11a interaction (200–500 nM) (Shimaoka et al, 2001; Tominaga et al, 1998) and within the range for that reported for the ISG15-Influenza virus NS1B interaction (180 nM-1.9 μM) (Guan et al, 2011; Li et al, 2011). The binding of ICAM1 to the αI domain is dependent on the Metal Ion Dependent Adhesion Site (MIDAS), a group of residues that coordinate a magnesium ion at the ICAM1-αI interface (Shimaoka et al, 2003).…”
Section: Resultssupporting
confidence: 78%
“…Ac-AChBP was captured by nickel- (Ni-) charged resin (GE Healthcare) and eluted with 300 mM imidazole in Tris buffer (50 mM Tris, pH 8.0, 50 mM NaCl) then further purified by gel filtration chromatography using the Superdex 200 column (GE Healthcare) [20]. The detection wavelength was 280 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, a specific region of the viral NS1B protein inhibits covalent conjugation of ISG15 to target proteins by its influence on the first ISG15 conjugation step catalyzed by UBE1L, which is the E1 enzyme for ISG15 [82,83] . Also in this case, it is hard to say how the conjugation of ISG15 modulates the replication of human influenza B virus and what the real biological consequences of this process are.…”
Section: Influence Of Pathogens On Other Ubiquitin-like Modifiersmentioning
confidence: 99%